KAJIAN IRAMA SYAIR TRADISI BEJALI’ TAPAKNG GOLAUMALI SUKU DAYAK LINOH KABUPATEN SINTANG - Kristianus, Kristianus; Ismunandar, Ismunandar; Yery, Christianly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is the lack of interest of the younger generation against traditional arts which is a hereditary heritage of the ancestors and the need for an effort to learn and preserve the traditional music. One of the arts tradition that is almost extinct and began to be unknown by the community itself is the Bejali vocal music from Dayak Linoh tribe, Sintang district. The purpose of this research are: 1) Describing vocal music composition of Bejali Tapakng Golaumali tradition's lyric verse from Dayak Linoh tribe, Sintang district, 2) Describing the contextual aspect of Bejali' Tapakng Golaumali. The method used in this research is descriptive qualitative method and using ethnomusicology approach. The data contained in this study is the result of direct observation and interviews to informants in the form of Vocal Music Composition Bejali' Tapakng Golaumali, and contextual aspects of Bejali' Tapakng Golaumali. The data were analyzed qualitatively, with data source from Yustina Bayang, Dandui, Bantan and several other artists who actively participated and learned about the traditional vocal music, especially the vocal music of Bejali' from Dayak Linoh tribe, Sintang District. Â Based on data analysis, it can be concluded that Bejali' is one of the vocal music that how to sing it using ornaments, vibrato, and original Linoh language. The Bejali' poem is not standard (it is situational) and is spontaneously used in figurative words. Bejali' can be sung by men and women. Basically, Bejali' is sung as a means of marriage applications, cut teeth, and welcome guests Dayak Linoh. Bejali' is sung without any musical instrument. This research is expected to be a stimulus to the growing interest to learn the traditional vocal music, especially vocal music Bejali' from Dayak Linoh tribe, Sintang district. Â Keywords: Study, Poetry Rhythm, Bejali', Dayak Linoh, Sintang District.